The Role Of Digitalization In Enhancing Public Service Efficiency: Challenges And Opportunities In Managing Public Complaints Through E-Government In Indonesia - Vita Aprilina; Timbul Dompak; Lubna Salsabila; Karol Teovani Lodan (International Journal of Social Welfare and Family Law, 2025)
The digitalization of public services improves efficiency, openness, and accessibility, particularly in the administration of public grievances. Information and communication technology facilitates effective, rapid, and responsive complaint resolution while safeguarding user data security. This strategy promotes public engagement using digital channels, including web applications, social media, and unified online complaint mechanisms. Nonetheless, issues such as the digital divide, technological proficiency, and infrastructure preparedness must be resolved. This study utilizes a literature review methodology, employing documentation methodologies and content analysis. The results indicate that the use of e-Government in Indonesia has markedly enhanced the efficiency, openness, and accountability of public services. The use of technology enhances the administration of public grievances in accordance with principles of good governance and current rules. However, issues with infrastructure, human resources, and community engagement remain. To optimize its beneficial effects, initiatives should concentrate on improving technology infrastructure, advancing human resource skills, and amplifying public awareness of the advantages of e-Government. These approaches intend to enhance the system's efficacy in providing high-quality and responsive public services.